Hubungan Komunikasi Terapeutik Perawat dengan Tingkat Kecemasan pada Pasien yang Menjalani Hemodialisa - Listiana, Devi (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2020)
Hemodialysis is a process of cleansing the blood by accumulation of waste. Hemodialysis is used for patients with end-stage renal failure or patients with acute illness who need dialysis for a short time. This study aims to study the relationship of therapeutic communication with anxiety levels in hemodialysis patients in hospitals. Dr. M. Yunus Bengkulu City. This research is a quantitative study with cross sectional research design. Sampling in this study used an accidental sampling technique of 38 respondents. Data obtained directly by providing questionnaires and interviews. Data analysis using univariate and bivariate analysis. The results obtained: (1) Of the 38 respondents who did therapeutic communication as many as 27 people (71.1%), and who did not do therapeutic communication as many as 11 (28.9%). (2) From 38 respondents there were 20 people (52.6%) severe anxiety, 4 people (10.5%) moderate anxiety, 10 people (26.3%) mild anxiety, and 4 people (10.5%) did not there is anxiety. (3) There is a relationship between therapeutic communication and anxiety level in hemodialysis patients in the Hemodialysis Room of RSUD. Dr. M. Yunus Bengkulu, with p-value = 0.003 0.005. It is expected that health workers, especially nurses, use therapeutic communication techniques prior to hemodialysis to reduce the anxiety of patients who will undergo hemodialysis by providing more accurate information regarding actions to be taken to foster a relationship of trust between clients and nurses.Â Keywords: Therapeutic Communication, Anxiety Level, Hemodialysis